2010
DOI: 10.15288/jsad.2010.71.847
|View full text |Cite
|
Sign up to set email alerts
|

Romantic Relationship Status Changes and Substance Use Among 18- to 20-Year-Olds

Abstract: ABSTRACT. Objective: Changes in romantic relationship status are common in emerging adulthood and may be linked to changes in substance use. This study tested the hypothesis that entry into relationships or transitioning to a more committed status leads to decreases in substance use and that dissolution of relationships or transitioning to a less committed status results in increases in substance use. Method: Data were from a community sample of 939 individuals. Substance use (heavy drinking, marijuana use, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 36 publications
11
56
0
Order By: Relevance
“…We also found that alcohol problems increased for those who went from being in an exclusive relationship to being single. This is consistent with fi ndings that relationship dissolution in emerging adults is associated with increases in substance use, including heavy drinking (Fleming et al, 2010b), and that divorce is associated with increases in alcohol use and problems in adults (Horwitz et al, 1996;Overbeek et al, 2006;Power et al, 1999). Although we are unable to establish the direction of causality for this association, our fi ndings suggest that individuals experiencing relationship dissolution during the fi rst year of college may be at an elevated risk for alcohol problems.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We also found that alcohol problems increased for those who went from being in an exclusive relationship to being single. This is consistent with fi ndings that relationship dissolution in emerging adults is associated with increases in substance use, including heavy drinking (Fleming et al, 2010b), and that divorce is associated with increases in alcohol use and problems in adults (Horwitz et al, 1996;Overbeek et al, 2006;Power et al, 1999). Although we are unable to establish the direction of causality for this association, our fi ndings suggest that individuals experiencing relationship dissolution during the fi rst year of college may be at an elevated risk for alcohol problems.…”
Section: Discussionsupporting
confidence: 87%
“…As noted earlier, marital dissolution is associated with increases in alcohol use and problems in older-adult samples, but whether the same is true for romantic relationships in emerging adulthood is less clear. Relationship problems are one of the top three reasons that college students seek university counseling services (Mistler et al, 2012), and retrospective data indicate that experiencing a breakup in emerging adulthood is associated with elevated levels of substance use (Fleming et al, 2010b). Identifying whether relationship dissolution is associated with prospectively measured changes in alcohol problems is of particular importance for understanding the potential clinical relevance of breakups for preventing or intervening with alcohol problems in this age group.…”
Section: Studies Of Nonmarital Romantic Relationshipsmentioning
confidence: 99%
“…Both a decrease in the number of cannabis-using peers and the act of moving in with a partner were linked to (a shift toward) nondependence. This is consistent with past research showing that protective mechanisms of romantic relationships are stronger in more serious relationships (Fleming, White, Oesterle et al, 2010) and that cohabitation is related to decreased use (Lonardo et al, 2010). Also, suggestibility emerged as an explanatory factor.…”
Section: Discussionsupporting
confidence: 91%
“…Drinking compatibility should be an important issue for unmarried romantic partners as well as married couples. Among dating couples, more congruent drinkers were characterized as having better relationship quality than discrepantly drinking partnerships (Fleming et al, 2010;Wiersma et al, 2009). These results may refl ect a more general phenomenon whereby partner similarity both attracts couples and reinforces couple behaviors.…”
mentioning
confidence: 99%
“…Relationship type differences are important to examine both as main effects and as potential moderators. But as Fleming et al (2010) acknowledged, little research has examined whether alcohol use plays a role in the relationship quality and dissolution of dating or cohabiting relationships.…”
mentioning
confidence: 99%